Introduction: Thinking Politically with Popular Music of the Balkans - Baker, Catherine (Routledge, 2024)
The introduction surveys the sociopolitical contexts surrounding historic and contemporary popular music in the Balkans. It explains the complexities of ‘popular music’ and other related terms in defining the field of study, including the problems of mapping anglophone concepts and terminology onto Balkan cultural contexts, and offers an overview of how research into popular music and politics in the Balkans has developed since the groundbreaking studies of the 1990s. It explains key choices in framing the volume by raising questions such as how ‘the Balkans’ and their boundaries might be defined in studying popular music; how to overcome the challenges of methodological nationalism; how to account for transnational connections that go beyond the Balkans; the impact of emerging themes such as global raciality and coloniality, the political economy of technology, and the repercussions of Russia’s full-scale invasion of Ukraine; and how popular music scholars’ ways of researching and knowing might make distinctive and equitable contributions to knowledge production about the region more widely.